Freud in a Fairy-Tale Perspective - Vaz da Silva, Francisco (Annual Meeting of the American Folklore Society, 2001)
Insofar as the theoretical founding block of psychoanalysis—the Oedipus complex—is itself drawn from folklore, one may ask whether or not astounding confluences to be found between Freud’s reasoning and conclusions on the one hand, and deep strands of fairy-tale themes on the other, could stem from Freud’s use of a folkloric theme to make sense of clinical data. In other words, is the theoretical basis of psychoanalysis an extraordinary variation on a traditional theme of folklore? If so, what inferences can one draw?